Britain From Above - Harrison, Ian; Foreword by Marr, Andrew (London Pavilion Books, 2008)
The book features exclusive, awe-inspiring photography from the programme, as well as computer simulations charting Britain's natural history, its industry and transport systems, natural heritage and archaeology. Britain From Above represents the landscape of a nation as it's never been seen before.
Include Color Illustrations and Index.
Keywords: Landscapes -- Great Britain -- Geography